2013
DOI: 10.1093/qjmed/hct093
|View full text |Cite
|
Sign up to set email alerts
|

Relative and attributable diabetes risk associated with hyperuricemia in US veterans with gout

Abstract: Background: Hyperuricemia is known to be a risk factor for incident type 2 diabetes mellitus, but the absolute magnitude of the association is not known. We aimed to evaluate the strength of association between hyperuricemia and the risk of developing diabetes among the US veterans with gout.Methods: Patients (age ≥ 18 years) with ≥2 clinical encounters with gout diagnoses, no history of inflammatory diseases or diabetes and two serum urate (sUA) measurements between 1 January 2002 and 1 January 2011 were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…Unlike previous studies, this study excluded the obesity, hyperlipidemia, hypertension, etc., which could be better re ect the differences of the above three groups metabolites. We still observed that blood glucose and systolic blood pressure were higher in the gout or hyperuricemia groups than in the healthy controls, which indicated that uric acid was related to glucose and salt metabolism [12][13][14][15].…”
Section: Discussionmentioning
confidence: 78%
“…Unlike previous studies, this study excluded the obesity, hyperlipidemia, hypertension, etc., which could be better re ect the differences of the above three groups metabolites. We still observed that blood glucose and systolic blood pressure were higher in the gout or hyperuricemia groups than in the healthy controls, which indicated that uric acid was related to glucose and salt metabolism [12][13][14][15].…”
Section: Discussionmentioning
confidence: 78%
“…Our data indicate all-cause and CVD mortality risks elevated across UA levels in non-diabetes adults, but the U-shaped relationship between UA level and all-cause mortality is reflected in the participants with diabetes ( Table 3). It is still debated whether hyperuricemia is an independent risk factor for CVD or merely associated with other risk factors, including hypertension [25], renal disease [26], hyperlipidemia [27], and diabetes [28]. In patients with gout, ULT would be cost-effective [22].…”
Section: Discussionmentioning
confidence: 99%
“…Since the increase of SUA concentration resulted in risk for developing T2DM, large numbers of studies have linked HUA with T2DM [7,22]. Many researches had demonstrate that approximately 8.7% of all new cases of T2DM were statistically ascribed to HUA [23,24]. Ogbera et al reported a 25% prevalence of HUA in Nigerian patients with T2DM, while in Chinese T2DM patients, HUA prevalence was 36.1% in women and 28.4% in men [25,26].…”
Section: Discussionmentioning
confidence: 99%